Islam, women, and violence in Kashmir : between India and Pakistan - Khan, Nyla Ali, 1972- (Comparative feminist studies series., 2010)
"Since 1989, religious fundamentalism and exclusionary nationalism in Indian administered Jammu and Kashmir have generated political and social turmoil that has eroded the ethos and fabric of Kashmiri culture. These forces are responsible for the silencing of dissenters, economic deprivation, lack of infrastructure, mass displacements, political anarchy, and repression of women. This book seeks to analyze the effects of nationalist, militant, and religious discourses and praxes on a gender-based hierarchy"--Provided by publisher